2021
DOI: 10.1101/2021.04.09.439217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thyroid hormone regulates abrupt skin morphogenesis during zebrafish postembryonic development

Abstract: Thyroid hormone is a key regulator of post-embryonic vertebrate development. Skin is a biomedically important thyroid hormone target organ, but the cellular and molecular mechanisms underlying skin pathologies associated with thyroid dysfunction remain obscure. The transparent skin of zebrafish is an accessible model system for studying vertebrate skin development. During post-embryonic development of the zebrafish, scales emerge in the skin from a hexagonally patterned array of dermal papillae, like other ver… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 83 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…We have shown that hypoTH fish lack superficial dermal cell types at the stage sampled for sequencing, though these cell types do appear later in development (Aman et al, 2021). To confirm the presence of residual, pre-SFC in eda mutants, we imaged live fish expressing ET37:EGFP, which enables visualization of all dermal cells (Parinov et al, 2004;Aman et al, 2021). Indeed, eda mutants exhibited a mat of ET37:EGFP+ dermal cells-presumptive pre-SFC-beneath the epidermis that was not present in hypoTH fish (Fig 3B).…”
Section: Eda-edar-nf-kb and Thyroid Hormone Regulate Basal Epidermal Gene Expression Associated With Dermal Morphogenesismentioning
confidence: 81%
See 4 more Smart Citations
“…We have shown that hypoTH fish lack superficial dermal cell types at the stage sampled for sequencing, though these cell types do appear later in development (Aman et al, 2021). To confirm the presence of residual, pre-SFC in eda mutants, we imaged live fish expressing ET37:EGFP, which enables visualization of all dermal cells (Parinov et al, 2004;Aman et al, 2021). Indeed, eda mutants exhibited a mat of ET37:EGFP+ dermal cells-presumptive pre-SFC-beneath the epidermis that was not present in hypoTH fish (Fig 3B).…”
Section: Eda-edar-nf-kb and Thyroid Hormone Regulate Basal Epidermal Gene Expression Associated With Dermal Morphogenesismentioning
confidence: 81%
“…Based on these findings, we predicted that hypodermis would be malformed or missing in live bnc2 mutants. To test this prediction and validate inferences from the single cell transcriptome data, we imaged the dermis of live animals expressing ET37:EGFP, expressed broadly across dermal cell types (Aman et al, 2021). In wild-type controls, the hypodermis appeared as a thin, nearly confluent cell layer deep in the dermis, whereas in bnc2 mutants no such layer was apparent, instead the deepest dermis appeared to contain only dermal mesenchyme (Fig 4D; Fig 4 S1A; Fig 1 S1B).…”
Section: Hypodermal Contribution To the Stripe-forming Pigment Cell Microenvironment And Iridophore Differentiationmentioning
confidence: 95%
See 3 more Smart Citations